The Role of Non-Government Organizations in the Education of Migrant Workers’ Children in Sabah Malaysia - Muslihudin, Muslihudin; Hussin, Rosazman; Retno Wulan, Tyas; Santoso, Jarot (KnE Social Sciences, 2023)
The number of Indonesian Migrant Workers (IMWs) in Malaysia is at the highest compared to other countries. Most IMWs in the states of Sabah and Sarawak are illegal migrants though they have lived in Malaysia for decades, some for up to three generations. Thus, many of their children have also been born and raised in Malaysia. There is a serious problem regarding the education of their children. The Malaysian government does not acknowledge this because the children are not citizens. The Indonesian government is also very limited in its ability to facilitate aid to these children because there are over 50 thousand of them. This article aimed to determine whether non-governmental organizations (NGOs) are concerned and what their role is in helping to overcome the education problems of IMWs children, especially those in the Sabah region of Malaysia. The method used in this study is qualitative. Data collection by interview method, focus group discussion offline and online via zoom, and documentation. Data analysis was carried out interactively. The results indicate that NGOs play a significant role in the education of IMW’s children. There are 2 NGOs play a role: the first NGO, Humana, at the elementary school level in Sabah, Malaysia. Humana NGO resources are various stakeholders in Sabah Malaysia. Second, the NGO Sabah Bridge plays a part from junior high school level education to Senior high school level. The NGO Sabah Bridge’s resources are teachers sent from Indonesia to Malaysia and former teachers who have returned to Indonesia. Keywords: Non-governmental organizations, children, education, Sabah